The Impact of Trade Openness and Political Stability on Food Security: A Panel Data Analysis for Selected Countries - Canan Özge Eğri (İktisat Politikası Araştırmaları Dergisi)
Food security is a pressing global concern influenced by various factors, including commercial openness and political stability. This study employs panel data analysis to investigate the impact of commercial openness and political stability on food security in selected countries. Panel data analysis offers advantages over cross-sectional or time series methods by providing greater flexibility, enhancing estimation reliability, and addressing issues like multicollinearity. Thisstudy explores the intricate relationships between commercial openness, political stability, and food securityby utilising a unified framework of econometric methods, including likelihood and two-stage least squares. The analysis also focuses on mitigating the endogeneity bias using empirical moments. In this research, the study explores the influence of trade openness and political stability on food security. While previous literature has separately examined the relationships between food security and political stability, as well as food security andglobalisation, there needs to be a morecomprehensive analysis integrating both aspects to understand their combined impact on food security. Therefore, the research aims to address this gap by investigating the relationship between political stability and trade openness and food security. The study uses a model tested with data from 96 countries using the Generalised Method of Moments (GMM) method. The subsequent sections of the study, specifically chapters 2 and 3, thoroughly analyse the variables under discussion. The findings of the model and the ensuing discussions are then presented. The findings from this study contribute to a deeper understanding of how commercial openness and political stability affect food security, providing valuable insights for policymakers and researchers striving to enhance global food security.